Uji Pengaruh Pelet Pupuk Hayati VP3 dengan Tambahan Cangkang Telur terhadap Viabilitas Bakteri Fungsional dan Bibit Tanaman Tomat (Solanum lycopersicum L.) - Amanda Reha Zahran; Novi Arfarita; Mahayu Woro Lestari (Universitas Islam Malang, 2023)
This research was conducted to determine the effect of different drying temperatures on the total viability of VP3 bio-pellet fertilizer bacteria and to determine the effect of eggshell composition and VP3 bio-fertilizer formulation in pellets on the growth of tomato plant seedlings. This research was conducted at the Central Laboratory and Halal Center, Islamic University of Malang from June until September 2022. This study used a Completely Randomized Design (RAL) on the viability test of VP3 biological fertilizer pellet bacteria with a total of 12 treatments and repeated 3 times and Randomized Group Design (RAK). ) In the tomato plant seed test consisted of 4 treatments and was repeated 5 times. Observational data were analyzed using the 5% level F test (ANOVA). If there is a significant effect, a further test is carried out with a BNT level of 5%. The results of the bacterial viability test showed that the V3T1 treatment (15% Eggshell Waste + VP3 with a drying temperature of 40oC) had an average total bacterial viability that was not significantly different from the V1T1 treatment (5% Eggshell Waste + VP3 with a drying temperature of 40oC) and V2T1 (10% Egg Shell Waste + VP3 with drying temperature 40oC). The results of the tomato plant seed test showed that the V3T1 treatment (15% Egg Shell Waste + VP3 with a drying temperature of 40oC) had a significant effect on the height of the tomato seedlings and the fresh weight of the tomato seedlings while the best root length of the tomato seedlings was in the V2T1 treatment (Waste Shells). Egg 10% + VP3 with drying temperature 40oC). Keywords: VP3 bio-pellet fertilizer, bacterial viability, tomato seed